Comprehensive preclinical studies on the bioactivity of Orbignya phalerata Mart. (Babassu) and its derived products: a systematic review - Nicole Debia; Isione Oliveira Castro; Ana Beatriz Santana Sousa; Victor Alves de Oliveira; Helber Alves Negreiros; Paulo Michel Pinheiro Ferreira; João Marcelo de Castro e Sousa (SpringerOpen, 2024)
Abstract Background Babassu (Orbignya phalerata Mart.) is a palm tree well distributed in Latin America, whose fruit has a mesocarp and kernel used for human feeding, and empirically related to the treatment of gastritis, vaginitis, and wound healing. Main body of the abstract The activities attributed to babassu can guide new research on health applications and, for this reason, this study aimed to report in vitro and in vivo biological activities of O. phalerata constituents through a systematic review. Searches terms were applied in five world databases and the data from the publications were collected according to PICOS criteria, including the fruit component, concentration/dose, time of exposure, and comparative groups. All outcomes were reported and the most relevant outcomes were described by a narrative synthesis and a risk of bias assessment. A total of 28 in vitro (n = 15) and in vivo (n = 11) studies were included, and two showed both experimental designs. The studies were heterogeneous, with the predominance of metabolic analysis, wound and peptic ulcer healing, besides in vivo toxicity, among others. For in vitro analysis, antioxidant tests, cell viability and antimicrobial activity predominated. All in vivo ones used rodents. Meanwhile, tumor and non-tumor cell lines, bacteria strains, Leishmania amazonensis, Artemia salina, and antioxidant reactions were considered for in vitro protocols. Short conclusion The most frequent applications included mesocarp and kernel in a wide range of extracts, emulsions, and concentrations. Their low in vitro lethality and cytotoxicity, and no acute toxicity in vivo open possibilities for the development of long-term toxicity assays with repeated doses in rodents and interventions in clinical trials. Graphic abstract